The Comparative Efficacy and Safety of Entecavir and Lamivudine in Patients with HBV-Associated Acute-on-Chronic Liver Failure: A Systematic Review and Meta-Analysis - Jiao Yang; Hang Sun; Qi Liu (Gastroenterology Research and Practice)
Background. Currently, both of entecavir and lamivudine are effective for patients with HBV-associated acute-on-chronic liver failure (ACLF). However, there is no consensus on the efficacy of entecavir versus lamivudine for patients with HBV-associated ACLF. The aim of the study was to compare the efficacy and safety of entecavir with that of lamivudine for HBV-associated ACLF patients. Methods. Publications on entecavir versus lamivudine in HBV-associated ACLF patients were comprehensively identified. Odds ratio and mean difference were used to measure the effect. Results. Ten studies, totaling 1254 patients, were eligible. No significant differences between the two drugs presented in the 1-, 2-, 3-, or 6-month survival rates. However, after 12 months of treatment, patients prescribed entecavir had a statistically higher survival rate (p=0.008) and lower total bilirubin (p<0.0001) and alanine aminotransferase (p=0.04) levels compared to patients prescribed lamivudine. More patients achieved HBV negative levels when taking entecavir as measured at 1-, 3-, and 12-month time points and had a lower rate of HBV recurrence. Conclusion. While entecavir and lamivudine are both relatively safe and well tolerated, entecavir was more efficacious in terms of survival rate and clinical improvement in long-term treatment. Further prospective randomized controlled trials are needed to validate these results.